Sejarah Hubungan Habaib dan Nahdlatul Ulama (NU) - Alatas, Ismail Fajrie; As'ad, Muhammad; Karyadi, Fathurrochman (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
The relationship between Bani Alawi (Ba 'Alawi) and the ulama of Nahdlatul Ulama (NU) has been documented in many historical records of Indonesia. However, how the relationship started and for what motive is not yet known. In this edition, the editorial team of the Tebuireng Journal of Islamic Studies (TJISS) publishes an edited transcript of a webinar on the history of the relationship between Habaib and NU which was held on December 20, 2020, by the Faculty of Islamic Studies (FAI), Universitas Hasyim Asy'ari (Unhasy). This transcript is the presentation of Ismail Fajrie Alatas, one of the editorial boards of TJISS, who currently works as Assistant Professor of Middle-Eastern & Islamic Studies at New York University, United States. Alatas has written many academic works in the form of books and journals with a focus on the theme of Islam in the Indian Ocean world particularly, the historical and contemporary connections between Southeast Asia and South Arabia. Alatasâ€™ writings examine the intersections of religious authority, social formation, mobility, semiotics, and communicative practice with a focus on Islamic Law, Sufism, and the Hadrami diaspora in Indonesia (that is, those who trace their origins to the Hadramawt valley of Southern Yemen). In the discussion held in the webinar, Alatas explained that the initial relationship between Habaib and the ulama who later founded the organization of Nahdlatul Ulama was formed as a challenge to the Islamic court-style of â€œJavanese Islamâ€ that dominated the archipelago in the 18th and 19th centuries.